Risk biomarkers enable precision in public health. (29th June 2018) - Ollier, William; Muir, Kenneth R; Lophatananon, Artitaya; Verma, Arpana; Yuille, Martin
Precision medicine uses biomarkers to diagnose disease. However, they can also be used to measure risk of disease. Thus, biomarkers herald a new addition to public health – Precision Public Health. We examine the implications. Risk biomarkers are identified by analyzing population cohorts. They constitute risk factors in mathematical 'Disease Risk Models'. The risk may be fixed as in a genetic biomarker or variable as in some protein biomarkers. They help monitor current risk of disease in an individual, thereby aiding efforts to reduce risk. In the UK, the NHS Health Check system is a universal system for assessing risk and for risk reduction. The system can now make use of modern biomarkers once appropriate infrastructure and governance are in place.